2018
DOI: 10.1016/j.jneuroim.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological characteristics of neuromyelitis optica spectrum disorder in the North Egyptian Nile Delta

Abstract: This is the first NMOSD case series in Egypt. Despite some limitation in testing and access to care, there are features of our NMOSD cases that appear to be different from other worldwide cohorts reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 33 publications
9
22
1
Order By: Relevance
“…The NMOSD cohort at our institution was predominantly female with an average of 30 years, which is in keeping with what has been found in other studies from Africa [ [13] , [14] , [15] , [16] , [17] ]. Similarly, ON and LETM were the most frequently reported symptoms at relapse presentation, with LETM being the most frequent overall (73%, and the Algerian cohort was 75% [ 17 ]), but the concomitant optico-spinal involvement i.e.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The NMOSD cohort at our institution was predominantly female with an average of 30 years, which is in keeping with what has been found in other studies from Africa [ [13] , [14] , [15] , [16] , [17] ]. Similarly, ON and LETM were the most frequently reported symptoms at relapse presentation, with LETM being the most frequent overall (73%, and the Algerian cohort was 75% [ 17 ]), but the concomitant optico-spinal involvement i.e.…”
Section: Discussionsupporting
confidence: 88%
“…All patients were also commenced on immunosuppression, with mycophenolate and azathioprine being used in the majority of cases as is recommended by NMOSD treatment guidelines [ 5 ], chiefly because of their affordability and availability. In other African cohorts, cyclophosphamide is used more often [ 14 , 15 ], which we tend to avoid given the implications to fertility in a female-predominant disease. Rituximab is generally expensive and not easily available, and was only used in the management of case 8 as they did not like to daily tablets; it is used more frequently for NMOSD in other parts of Africa especially Egypt [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, three other patients had a family history of autoimmune disorders. Not only the associated immunologic disorder had been observed, but also positive ANA test was found in 6 patients, two of them also had seropositive for the AQP4 antibody, and anti-ds-DNA was the only weak positive result in one patient [29].…”
Section: Pattern Of Nmosd In the Egyptian Populationmentioning
confidence: 99%
“…1 The knowledge about NMOSD has been expanding over the last few years and several studies have been conducted in different nations over the globe to describe various phenotypic and radiological lineaments. [7][8][9] Recent studies demonstrated the presence of IgG antibodies to myelin oligodendrocyte glycoprotein (MOG-IgG) in a subset of patients with seronegative NMO. 7,[10][11][12] It was thought that anti-MOG disease primarily affects pediatric cohorts, and has a monophasic course with predilection to optic pathways.…”
Section: Introductionmentioning
confidence: 99%